Association of Gender With Outcomes in Hospitalized Patients With 2019-nCoV Infection in Wuhan - Han, Huiwu; Peng, Xiaobei; Zheng, Fan; Deng, Guiyuan; Cheng, Xiaocui; Peng, Liming (Frontiers in Public Health, 2021)
Aim The aim of this study was to analyze the association of gender with psychological status and clinical outcomes among patients with 2019-nCoV infection to provide new directions for the prevention and control of the pandemic. Methods 138 patients with confirmed 2019-nCoV infection at Wuhan Union Hospital, between February 8 and March 31, 2020, were included in the study analysis. General information and data on clinical characteristics were collected from patients’ medical records. Participants’ responses to self-report measures of psychological status were also collected. Results Anxiety levels, depression levels, and recovery rates were significantly higher among women compared to men. Conversely, chronic disease history and smoking rates, dry cough incidence, C-reactive protein levels, and disease severity were significantly higher among men than women (p < 0.05). Conclusion Female patients experienced more severe psychological issues, due to higher levels of anxiety and stress, than male patients; indicating that more attention should be paid to the psychological care of female patients. In contrast, the general condition of male patients was more severe, particularly among elderly male patients with a history of chronic disease and smoking, suggesting that, to prevent and control 2019-nCoV infection, male patients should be encouraged to quit smoking as soon as possible to reduce the risk of severe pneumonia.